The University of Louisville - Cox, Dwayne, 1950- (Book collections on Project MUSE., 2000)
Dwayne Cox and William Morison trace the twists and turns of the University of Louisville's two hundred year journey from provincial academy to national powerhouse. From the 1798 charter that established Jefferson Seminary to the 1998 opening of Papa John Stadium, Cox and Morison reveal the unique and fascinating history of the university's evolution. They discuss the early failures to establish a liberal arts college; tell the extraordinary story of the Louisville Municipal College, U of L's separate division for African Americans during the era of segregation; detail the political wrangling a.